Persepsi terhadap Motivasi Berjilbab Mahasiswi PGMI STIT Al Fattah - Nur Ilahin (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
In everyday life, it is still rare for women to wear the hijab. The main obstacle is the social aspect. Many people feel ashamed and even feel inferior when wearing Muslim clothing in their association. This is due to the influence of the environment that is difficult to avoid, this perception makes the writer want to know how the motivation of female students in veiling, especially for PGMI STIT Al Fattah students in hijab. The data used as a guide in this research are facts in the field, then processed and analyzed descriptively, which provides an interpretation of the objects that have been explained in language relevant to the direction of the research. This study concludes that there are several student motivations in using the hijab in daily activities, either motivation within the student itself or from extrinsic factors in the student's daily life environment. The motivation of PGMI STIT Al Fattah students in wearing the hijab is because on the basis of fulfilling their obligations for theological reasons (read; religion) than they wear the hijab on the basis of the provisions or encouragement of others.